PERFORMANCE ANALYSIS OF TOY COMPANIES USING BALANCED SCORECARD METHOD INTEGRATED WITH OMAX AND TLS (Case Study: PT. X) - Andre Vendi Pradana; Minto Waluyo (Journal of Industrial Engineering Management, 2023)
PT. X is a company engaged in the toy industry. Located in Surabaya, this company has the vision to become a quality and professional toy manufacturer. Along with the increasingly intense competition in the industrial world, every company must compete to improve its performance evenly. So far, the performance measurement conducted by PT. X only tends to financial measures, so other factors receive less attention. It will impact delays in the process of achieving the vision set by the company. Against the background of these problems, it is necessary to conduct a thorough performance appraisal using the balanced scorecard method integrated with the factual matrix (OMAX). PT.X Performance Evaluation Results using the balanced scorecard method weighted 16 key performance indicators (KPI) with the Objective Matrix (OMAX). 4 KPIs belong to the green category, which means that they have exceeded the target, 7 KPIs belonged to the yellow category, which means that it needs to be improved so the performance can be improved according to the targets expected by the company, and 5 KPIs belonging to the red category which means it needs special attention to get it immediately corrective action.